Menceritakan Bancah Birunguik, Memperagakan Silek Luncua Mendendangkan Balam-balam : Pelatihan Repertoar Baru Randai di Solok Selatan - Dede Pramayoza; Emri Emri; Susas Rita Loravianti (Abdi Seni, 2022)
This paper describes the implementation of the Randai Creation Workshop in South Solok Regency, which was carried out by ISI Padangpanjang Community Service Team. The workshops are carried out with problems solving approach and artistic research, which are oriented towards finding answers to problems through the practice of artwork creation. The process of creating Randai began with shared research for folklore that developed in South Solok, using the Focus Group Discussion (FGD) method, which resulted in findings in the form of the Bancah Birunguik story, which was then processed together as a screenplay. The process of creating Randai continued with the creation of Legaran with the method of practical mentoring, which departed from the repertoire of Silek Luncua, a silek genre that developed in South Solok. The last process of the workshop, also employing the method of practical assistance, is the blending of movements with sounds. This process is codified as an aspect of Randai musicality, using the Balam-Balam sung from Saluang Panjang tradition, a type of South Solok traditional song, as the main guide. The results of the workshop are several scenes of Randai as an embryo that can be developed into the typical Randai repertoire of South Solok.